The Role of Learning Media on Student Learning Outcomes in Fine Arts Subjects Two-Dimensional and Three-Dimensional Fine Art Materials for Grade IV SD Negeri Salamsari - Dwina Widyaning Lestari; Deni Setiawan (Jurnal Penelitian Pendidikan, 2026)
This study aims to describe the role of learning media in improving students' learning outcomes in Art Education, particularly on two-dimensional and three-dimensional art materials for fourth-grade students at SD Negeri Salamsari. This research employed a qualitative approach using a case study design. The research subjects consisted of a fourth-grade teacher and 24 fourth-grade students. Data were collected through interviews, observations, and documentation using triangulation techniques. The results indicate that the use of varied learning media, including concrete media, digital media, and teacher-made media, plays a significant role in enhancing students' learning outcomes across cognitive, psychomotor, and affective domains. Learning media help students understand abstract art concepts more concretely, improve artistic skills, and increase learning motivation and appreciation of art. Supporting factors in the implementation of learning media include the availability of school facilities, institutional support, and students' enthusiasm, while inhibiting factors include technical constraints, limited learning tools, time management issues, and teachers' administrative workload. Therefore, learning media are essential in improving the quality of art learning in elementary schools.